2006
DOI: 10.3201/eid1209.060361
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistantMycobacterium tuberculosis, Bangui, Central African Republic

Abstract: We investigated multidrug-resistant (MDR) Mycobacterium tuberculosis strains in Bangui, Central African Republic. We found 39.6% with the same spoligotype and synonymous single nucleotide polymorphism in the mutT1 gene. However, strains had different rpoB mutations responsible for rifampin resistance. MDR strains in Bangui may emerge preferentially from a single, MDR-prone family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…It has been discovered that many of these drug-resistant strains carry mutations in DNA repair genes, resulting in their mutator phenotype. ada/alkA, ogt [94,101] and ung [101] mutations have been discovered in Haarlem lineages, whereas mutT4, mutT2 and ogt have been discovered in W-Beijing lineages [100,102]. The same mutations are also observed in non-MDR strains, but this does not negate the point that their mutator phenotype may increase the possibility of them acquiring mutations against anti-tubercular drugs.…”
Section: Mycobacteria Chemotherapy and Evolutionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been discovered that many of these drug-resistant strains carry mutations in DNA repair genes, resulting in their mutator phenotype. ada/alkA, ogt [94,101] and ung [101] mutations have been discovered in Haarlem lineages, whereas mutT4, mutT2 and ogt have been discovered in W-Beijing lineages [100,102]. The same mutations are also observed in non-MDR strains, but this does not negate the point that their mutator phenotype may increase the possibility of them acquiring mutations against anti-tubercular drugs.…”
Section: Mycobacteria Chemotherapy and Evolutionmentioning
confidence: 92%
“…Finally, mutations to DNA damage repair proteins can lead to an increase in the mutation rate, as has been observed upon deletion of ung, uvrB, uvrD, fpg and udgB in Ms and ada/alkA together with ogt in MTB (Table 4 and Supplementary Table S3 at http://www.clinsci.org/cs/119/cs1190187add.htm). Furthermore, mutY [93] and mutT1 [94] mutations have been observed in drug-resistant phenotypes. Analysis of isoniazid-resistant strains has suggested that the SNPs responsible for resistance had arisen independently [82].…”
Section: Mycobacteria Chemotherapy and Evolutionmentioning
confidence: 99%
“…Ninety percent of tuberculosis cases occur in developing countries due to inadequacies in the healthcare resources and patient follow-up [5]. The problem became global with the emergence of multidrug resistant strains of Mtb (MDR-TB), which currently are reported in all countries with the burden of disease not witnessed since before the advent of antibiotics [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…While studying the genetic diversity of M. tuberculosis isolates in the Central African Republic (CAR), we described an MDR-prone family characterized by a T family spoligotype and a synonymous variation in the DNA repair gene mutT 1 [8]. This prompted us to screen our set of well-defined isolates from CAR [8,9] by sequencing putative anti-mutator genes including ada/alkA to identify other variations that could be markers of relevant clinical strains.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted us to screen our set of well-defined isolates from CAR [8,9] by sequencing putative anti-mutator genes including ada/alkA to identify other variations that could be markers of relevant clinical strains.…”
Section: Introductionmentioning
confidence: 99%